1980
DOI: 10.1038/ki.1980.147
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic studies in IgA nephropathy

Abstract: Circulating immune complexes (CIC) were detected in 43.6% of 78 patients with primary IgA nephropathy by the solid-phase Clq radioimmunoassay. The IC were intermediate (9 to 17S) in size and contained IgA, IgG, and less commonly IgM. CIC were often present intermittently, correlating with episodes of macroscopic hematuria. Elevated serum IgA concentrations (38.7%) did not correlate with the detection of CIC. Similar findings were observed in sera samples from patients with Henoch Schonlein purpura and in IgA g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
2

Year Published

1982
1982
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(61 citation statements)
references
References 22 publications
4
55
0
2
Order By: Relevance
“…PH also decreases small intestinal motility promoting bacterial overgrowth [31,32] , while in the same time increases intestinal permeability [33] . In this regard, increased circulating IgA and IgAIC may represent an exaggerated response of immune system to excess gut antigen exposure [34,35] , resulting from diminished mucosal integrity and spillage of IgA into the circulation. Another mechanism could involve the endotoxemia that frequently accompanies LC with PH [36] , suggested to be generated by gut flora through bacterial translocation [37,38] favored by dysfunction of intestinal barrier [33,37] .…”
Section: Discussionmentioning
confidence: 99%
“…PH also decreases small intestinal motility promoting bacterial overgrowth [31,32] , while in the same time increases intestinal permeability [33] . In this regard, increased circulating IgA and IgAIC may represent an exaggerated response of immune system to excess gut antigen exposure [34,35] , resulting from diminished mucosal integrity and spillage of IgA into the circulation. Another mechanism could involve the endotoxemia that frequently accompanies LC with PH [36] , suggested to be generated by gut flora through bacterial translocation [37,38] favored by dysfunction of intestinal barrier [33,37] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested a basic dysregulation of IgA production by showing increased serum levels of IgA, IgA-containing immune complexes, and pIgA, and enhanced IgA-specific T helper activity in human patients (10)(11)(12). T cells are implicated in the pathogenesis of this disorder; however, the direct role of T cells in the pathogenesis of IgAN is unclear, as few T cells can be identified in glomerular mesangium.…”
Section: Introductionmentioning
confidence: 98%
“…Five, 10,20,25,30, and 50 days after the initiation of BrdU administration, the mice were sacrificed and intestinal LP lymphocytes were isolated. The LP lymphocytes were stained for membrane IgA (mIgA) and cytoplasmic BrdU by the method described previously with minor modifications (21).…”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…IgA nephropathy is the most common form of human glomerulonephritis worldwide, characterized by the deposition of IgA in the glomeruli (9). Although the mechanism of human IgA nephropathy has not been fully elucidated, high serum IgA levels, enhanced IgA-specific Th cells, and diminished numbers of IgAspecific regulatory T cells suggest that there is a basic dysregulation of IgA production in patients with this disease (10,11). Moreover, clinical association of relapses with mucosal infections, elevated serum Ab titers to respiratory pathogens, and dietary components in these patients indicate that mucosal immunity may also be involved in the pathogenesis of IgA nephropathy (12,13).…”
mentioning
confidence: 99%